Implementasi Konsep Pendidikan Karakter dalam Pembelajaran Tahfidz Al-Qur’an Maktab Terpadu Generasi Madani - Ade Salamun; Didin Hafidhuddin; Nirwan Syafrin (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
Childhood is often referred to as the golden age. At this time, the children are like a sponge who is very easy to absorb and remember all the information. One example is memorizing the Qur’an. If from an early age the child has been given a good education and taught about good character, then in the future the child will become a memorizer of the Qur'an (Qur’anic Tahfidz) who has spiritual and emotional intelligent and also has a superior character. Therefore, it is necessary to discuss the implementation of the concept of 9 pillars of character in learning tahfidz for early childhood. Therefore, this study aims to provide an overview of the process of implementing the concept of 9 pillars of character in tahfidz learning in Maktab Terpadu Generasi Madani. This study uses a descriptive method with a qualitative approach. The study found that the character education curriculum at Maktab Terpadu Generasi Madani does not really refer to the 2013 TK/PAUD National Curriculum nor the 9 pillars of character book in implementing character values to their students. However, the study conclude that the nine character pillars have been implemented in tahfidz learning at Maktab Terpadu Generasi Madani through hadith, daily prayers, and Islamic songs because the maktab has a book of Muatan Khas Maktab.